HISTORICAL NEED AND IDEOLOGICAL FOUNDATIONS OF THE DEVELOPMENT OF AESTHETIC CULTURE IN YOUTH (Scientific journal of the Fergana State University, 2023)
The article philosophically explores the role of history in the development of aesthetic culture of young people and its ideological aspects. It shows that the process of historical development was the basis for the formation of the national idea of Uzbekistan. At the same time, the impact of national ideas and ideology on the aesthetic culture of young people is expressed.